The Prognostic Significance of the Histological Types in Patients With Nonsmall Cell Lung Cancer ≤2 cm - Hao, Bo; Fan, Tao; Xiong, Juan; Zhang, Lin; Lu, Zilong; Liu, Bohao; Meng, Heng; He, Ruyuan; Li, Ning; Geng, Qing (Frontiers in Surgery, 2021)
Abstract Background: Few studies attempt to investigate the impact of histology on the outcome of NSCLC patients. In this study, we aim to whether the type of histology influenced the outcome of stage ⅠA NSCLC patients with tumor size(TS) ≤20mm. Methods: The data of the population in our study was collected from the Surveillance, Epidemiology, and End Results (SEER) Program which is supported by the National Cancer Institute of the United States. The primary outcome was overall survival (OS). Cox-regression proportional hazards models were performed to identify prognostic factors for OS. The secondary outcome was lung cancer-specific mortality (LCSM). A competing risk model was used to identify risk factors associated with LCSM. Results: A total of 4,424 eligible patients (T1a-bN0M0) who received sublobar resection (wedge resection (WR) and segmentectomy) were identified and included in the study for further analysis. For patients with TS ≤10mm, multivariate Cox-regression analyses for OS showed that lung squamous cell carcinoma (LUSC) yielded poorer OS compared with lung adenocarcinoma(LUAD), and no difference was observed between LUSC and LUAD for LCSM in competing risk models. For patients with TS>10mm&≤20mm, multivariate analyses revealed that LUSC patients experienced poorer OS compared to that of LUAD; the univariate competing risk analysis indicated SCC pathology predicted an increased risk of death from lung cancer, while no difference is observed in the multivariate competing analysis. In addition, segmentectomy was associated with longer OS in patients with >10mm &≤ 20mm but not in patients with≤10mm compared with WR. Conclusion: Our study demonstrated that squamous pathology was associated with the worse OS but not LCSM for patients with ≤20 mm compared with adenocarcinoma. Moreover, segmentectomy when compared to wedge resection appears to be associated with a better prognosis in patients with neoplasm >10 mm, but not in the case of nodule ≤10 mm.